The Processes of Students Thinking Based on Linguistic Intelligence on Straight-line Equations - Oktaviani, Lulu Eka; Prayitno, Lydia Lia (Universitas Muhammadiyah Surakarta, 2018)
This research is motivated by the students problem in solving the mathematic essay. Completing the story surely using the right steps to make the process work clearly. Linguistic intelligence can help students in solving the mathematic essay, because linguistic intelligence is an intelligence that can help students in understanding the story. The purpose of this research is to describe to Â process of students thinking in solving the essay based on linguistic intelligence. The research ia a descriptive qualitative which has main instrument is a researcher and supporting instrumentss is a identification of multiplle inteligence, essay test, and interview guidance.The results of this study indicate that the students with the lowest linguistic intelligence can only complete the stage of understanding the problem and devising a plan of the essay test. Students with the highest linguistic intelligence are be able to complete the stage of understanding the problem, devising of a plan, carring out of the plan, and looking back of the essay test. Â Keywords: Thinking Process, Linguistic Intelligence, Essay